Ge Hong. Famous Daoist Thinker & Practical Martial Artist - Stanley E. Henning (Universidad de León, 2012)
Ge Hong (284-363 CE) was an important intellectual figure of his time. He is known primarily for his interest in Daoist pursuits, including alchemy, as discussed in his writings titled One Who Embraces Simplicity (Baopuzi). However, the fact that he was also a military officer, who had practiced several weapons styles and who provides valuable insights into Chinese martial arts practices, has generally been ignored. This short article will attempt to outline Ge Hong's contributions to our understanding of the role of martial arts in Chinese culture and society based on his personal experience and observations. Ge Hong viewed the martial arts as practical skills related to hunting (archery) and self-defense, not Daoist pursuits, and he mentions that some of these skills could even be seen in children's play. His reference to Cao Pi (Emperor of Wei, 220-226 CE) sparring with General Deng Zhan reflects the place of martial arts among leadership in the political military system of early imperial China (206 BCE-960 CE). His explanation of oral formulas (koujue) is indicative of the secrecy maintained by martial artists concerning individual techniques.